2019
DOI: 10.1177/2325967119865500
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Distal Biceps Tendon Repair With and Without Concomitant Bicipital Aponeurosis Repair

Abstract: Background: The bicipital aponeurosis (BA) can often be torn concomitantly with a distal biceps tendon (DBT) rupture. Its repair, although recommended by some, has not commonly been addressed during the surgical management of DBT ruptures, and to date, surgical repair of the BA with DBT repair has not been evaluated clinically. Purpose: To utilize subjective and objective outcome measures to examine the safety and efficacy of 2-incision DBT repair with and without repair of the BA in patients with a DBT ruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Surgical treatment of BA may be required in various clinical situations, such as neurovascular entrapments, distal tendon rupture of biceps brachii, or spastic elbow deformity. Distal tendon rupture of the biceps brachii may be concomitant with a 45% association of BA tear (Luokkala et al, 2020; Midtgaard et al, 2020), and distal biceps brachii tendon repair with concomitant BA repair has better results than isolated distal biceps brachii tendon repair (Conlin et al, 2019). Neurovascular entrapments caused by BA are treated by BA release (Bassett 3rd et al, 1994; Bassett 3rd & Nunley, 1982; Seitz Jr. et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of BA may be required in various clinical situations, such as neurovascular entrapments, distal tendon rupture of biceps brachii, or spastic elbow deformity. Distal tendon rupture of the biceps brachii may be concomitant with a 45% association of BA tear (Luokkala et al, 2020; Midtgaard et al, 2020), and distal biceps brachii tendon repair with concomitant BA repair has better results than isolated distal biceps brachii tendon repair (Conlin et al, 2019). Neurovascular entrapments caused by BA are treated by BA release (Bassett 3rd et al, 1994; Bassett 3rd & Nunley, 1982; Seitz Jr. et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Landa et al [3] performed a cadaveric study and showed that termino-terminal sutures of the bicipital aponeurosis increased the mechanical strength in distal biceps tendon repair. Conlin et al [15] treated 24 male patients with a distal biceps tendon rupture. They reported that repair of the bicipital aponeurosis in conjunction with distal biceps tendon repair led to a faster return to activities compared with isolated tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LF repair with distal biceps brachii tendon compared to the distal biceps brachii tendon repair alone seems lead to faster return to recreational activities. Furthermore, the patients report a subjective improved pain and better strength [4]. All these arguments associated with finding that LF repair is a safe procedure taking only 5 min more than that of the biceps brachii tendon repair alone [4] should lead to the LF repair as much as possible.…”
Section: Lever Armmentioning
confidence: 97%
“…Furthermore, the patients report a subjective improved pain and better strength [4]. All these arguments associated with finding that LF repair is a safe procedure taking only 5 min more than that of the biceps brachii tendon repair alone [4] should lead to the LF repair as much as possible.…”
Section: Lever Armmentioning
confidence: 97%
See 1 more Smart Citation